Knowledge and practice on exclusive breastfeeding and association with work-related factors among mothers in Hospital Universiti Sains Malaysia - Rosdi, Nur Hanim Natasha Mohd (Universiti Sains Malaysia, 2024)
The process of feeding a baby breast milk straight from the mother's breast is known as breastfeeding. Exclusive breastfeeding is giving babies only breast milk and no other liquids or solids, except for necessary drugs or vitamins. During the first six months of a baby's life, this approach is advised entirely to provide the essential nutrients, antibodies, and immune support needed for the best possible growth and development. In addition to decreasing the risk of infections, it strengthens the link between mother and child, improving long-term health. This study seeks to assess the knowledge and practice of EBF among mothers in Hospital USM along with the association with work-related factors. A cross-sectional study was conducted on mothers given birth at HUSM in September 2023. Data for the study was collected using a self-administered questionnaire. A total of 152 working mothers fulfilled the inclusion criteria of the study and was selected through purposive sampling. Data collected were statistically analysed using the SPSS software version 27. The study used descriptive statistics and Pearson Chi-square. The results demonstrated 115 (75.7%) of participants have an excellent level of EBF knowledge and 91 (59.9%) of participants have an excellent level of EBF practice. Lastly, there were no association between three work-related factors [ working hours (p = 0.559), private room to express breastmilk (p = 0.233), maternity leave period (p = 0.697)] and level of EBF practice. in this study. However, there is a significant association between availability of refrigerator to store breastmilk and level of EBF practice (p = 0.011). In conclusion, these results highlight the necessity of focused workplace assistance initiatives to improve working mothers' EBF practice. Policymakers and healthcare practitioners can improve the availability of resources such as freezers for keeping expressed milk, so creating circumstances that favour prolonged exclusive breastfeeding.